ANALISIS MANAJEMEN RISIKO DALAM USAHA BUDIDAYA LOBSTER DAN DAMPAKNYA TERHADAP PENDAPATAN MASYARAKAT PEMONGKONG PERSPEKTIF EKONOMI ISLAM - Sapwan, Muhammad; Jalil, Muh. Rabbul (Fakultas Ekonomi Islam Institut Agama Islam Nurul Hakim Kediri Lombok Barat, 2024)
The natural wealth owned by the Pemongkong Village area, especially from the sea, should be able to boost the economy of the local community, namely by optimizing existing natural potential, such as in the lobster cultivation business. The method used in this research is qualitative with the research subjects focusing on 15 entrepreneurs who cultivate lobsters. The results of the research show that risk management in terms of capital for the people of Ujung Betok Hamlet is by borrowing from banks, cooperatives, and there are also those who owe money to collectors. To overcome these obstacles from the weather by not going to the cages when the wind is strong, as for problems from pests/diseases, the community prevents them by cleaning up leftover food that settles in nets, damaged nets, and feed. If viewed from an Islamic perspective, entrepreneurs are in accordance with the principles of Islamic economics which include halal types of business, implementing honesty, having the right to vote (khiyar) in choosing lobsters, setting prices transparently. The average income of the people of Ujung Betok Hamlet reaches more than IDR 100 million, and this income can improve the welfare of lobster farmers.